Better Not Forget : On the Memory of S&P 500 Survivor Stock Companies - Grobys, Klaus; Han, Yao; Kolari, James W. (MDPI, 2023)
This study explores the dependency structure of S&P 500 survivor stocks. Using a hand-collected sample of stocks that survived in the S&P 500 since March 1957, we employ rescaled/range analysis to investigate survivors. First, we find nonlinearities in the return processes of survivor stocks due to Paretian tails. Second, the return processes of very long-lived outliers exhibit long-term memories with Hurst exponents that significantly exceed one half on average. Third, sample-split tests reveal that the memory on average has virtually not changed over time—that is, survivor stocks do not forget. Fourth, and last, the long-term memory of survivor stocks appears to be unrelated to their exposures to traditional asset pricing risk factors.
Keywords: asset pricing; S&P 500 index; survivor stocks; Hurst exponent; Paretian tails; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|